Kajian Peran Pengembangan Masyarakat Dalam Mendukung Pariwisata Kampung Batik Rejomulyo Semarang - Radisa Chita Dewati; Mardwi Rahdriawan (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Semarang has a Kampung Batik which is a batik crafts center with Batik Semarangan as its main product. The Kampung Batik is located in Rejomulyo Village, East Semarang Sub District, Semarang. The development and management of the tourism sector in Kampung Batik is a form of tourism development based on community development. However, there are various problems in the development process, such as the lack of role of the Kampung Batik Association in encouraging the community and uniting batik artisans. Besides, limited funds, types of equipment, and places to hold pieces of training also add to the obstacles in tourism development. Most people in Kampung Batik who still think that the proceeds of batik activities do not add up to the cost of living, resulting in the people being reluctant to participate in developing Kampung Batik. The research method used is qualitative. The types of data collected are primary data, obtained through interviews and field observations, and secondary data acquired through literature review and documents analysis. The output of this study showed that tourism development in Kampong Batik was a tourism development based on community development carried out by various parties and then encourages participation from the local community and the realization of community empowerment efforts. Such community development plays a role in supporting tourism in Kampung Batik, namely improving the physical quality of the environment, creating togetherness and harmony between citizens, absorbing workforce in the tourism sector, providing tourist objects and attractions, and increasing the number of tourists.